Keratinolytic and Opportunistic Pathogenic Fungi from Carpet Dust in Mosques and Residentialhouses in Duhok, Kurdistan Region, Iraq - Hussein, Hend A.; Abdullah, Samir K. (Science Journal of University of Zakho, 2017)
One hundred samples of carpet dusts (50 samples from residential houses and 50 samples from mosques) were collected from different sites in Duhok province during the year 2014 to 2015 for the objective of the study of the occurrence of keratinolytic and other potentially pathogenic fungi using hair baiting method. A total of 24 fungal species (17 species from house dust) and (12 species from mosque dust) in addition to non-sporulating mycelia and yeasts were isolated and identified. The keratinolytic species Arthroderma cuniculi, Chrysosporium tropicum and Gymnoascus ressii were detected. Potentially pathogenic fungi in the genera Aspergillus, Arthrographis,Geomyces, Microascus,Scopulariopsis and Neoscytalidium were also able to colonize and grow on baited hairs.
Keywords: Keratinolytic fungi; opportunistic pathogens; carpet dust; Iraq